Avarol Effectively Inhibits Bacillus cereus Growth - Pejin1, B.; Kartali2, T.; Stanimirovic3, B.; Karaman2, M. (Asian Journal of Chemistry, 2014)
This work extends in vitro screening of antibacterial activity of avarol on four selected pathogenic bacteria associated with psoriasis (Bacillus cereus, Clostridium sporogenes, Enterococcus faecalis and Staphylococcus aureus). Avarol exhibited a moderate activity with minimum inhibitory and minimum bactericidal concentrations ranged from 0.78-1.56 and 3.12-18.75 μg/mL, respectively. It proved to be more effective against B. cereus in comparison to the both positive controls applied, gentamycin and ampicillin. According to the experimental data, this marine natural product may inspire development of new antibiotics with an enhanced therapeutic index, at first place those targeting B. cereus.